If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -4 = 3(2x + -1) Reorder the terms: -4 + 7x = 3(2x + -1) Reorder the terms: -4 + 7x = 3(-1 + 2x) -4 + 7x = (-1 * 3 + 2x * 3) -4 + 7x = (-3 + 6x) Solving -4 + 7x = -3 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -4 + 7x + -6x = -3 + 6x + -6x Combine like terms: 7x + -6x = 1x -4 + 1x = -3 + 6x + -6x Combine like terms: 6x + -6x = 0 -4 + 1x = -3 + 0 -4 + 1x = -3 Add '4' to each side of the equation. -4 + 4 + 1x = -3 + 4 Combine like terms: -4 + 4 = 0 0 + 1x = -3 + 4 1x = -3 + 4 Combine like terms: -3 + 4 = 1 1x = 1 Divide each side by '1'. x = 1 Simplifying x = 1
| (71-x)-x=7 | | 7x-2+6x+26=180 | | 16-4-Y=12-6 | | 5x^3-6x^2-23x-12=0 | | 2x(x)-4(x)=148 | | .25(2d+1)= | | 45j-6+1=108 | | 3x^2+7x=172 | | 5651.8116=2*3.14r^2+2*3.14*r*55.6 | | 5[3x-(-3-x)+2]=-4x-28 | | -3=3t-54 | | 5x-3x=13-5 | | (3x-35)+130=180 | | 0.5(-3a-7)-0.75(2a)=-a+7 | | 3w^3+21w^2+36w=0 | | x-(4)=15 | | (k-2)(7k-3)=0 | | 2-4=6 | | Cos^2x-1-sin^2x+sinx=0 | | 225+1=1+3x+1 | | 10-5=18 | | X^2-x+39=0 | | 2x+5y=2z | | 5p+38=-7(4+4p) | | 500-3a=200 | | a(a+1)=10 | | h=-9.8t+45t+1 | | 26=x-4 | | -6x+1=7(4x+5) | | 7y-6=15y+42 | | 3x^2-x-3=x^2 | | 12x-4x-9x^2=0 |